AESTHETIC EDUCATION OF MIDDLE CLASS STUDENTS BY MEANS OF EXPRESSIVE READING (Pedagogy of Higher and Secondary Education, 2004)
Different problems and aspects of bringing up of spirit among young generation in studiing Ukrainian literature are opened in this article.